2021
DOI: 10.1186/s13690-021-00649-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression remains a neglected public health problem among pregnant women in Northwest Ethiopia

Abstract: Background Antenatal depression is highly prevalent but a neglected public health problem in low income countries. It has serious effects on the general health of women, birth outcomes and child health. However, there has been limited substantial evidence on the prevalence and predictors of antenatal depression in Ethiopia. This lack of evidence potentiates the consequences of the problem and can limit the attention to intervention. Thus, this study aimed to assess the prevalence and potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…This finding indicates that the majority of the pregnant women in Saudi Arabia that go for antenatal care are young women between 25 and 35 years. This observation resonates with the findings in studies elsewhere [20,21] where the majority of the pregnant women seeking antenatal care are younger in age compared to the older ones.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding indicates that the majority of the pregnant women in Saudi Arabia that go for antenatal care are young women between 25 and 35 years. This observation resonates with the findings in studies elsewhere [20,21] where the majority of the pregnant women seeking antenatal care are younger in age compared to the older ones.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the prevalence of antenatal depression stands at 31.3% in mild depression, 23.9% in moderate depression, 5.5% in moderately severe depression, and 3.5% in severe depression. In a study by Beyene et al [20] where depression was not categorized, the prevalence of antenatal depression was found to be 24.45%. This observation is comparable to that of this current study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[8][9][10][11][12][13] In sub-Saharan African countries, prevalence rates have ranged from 17.7% to 50.0%. [14][15][16][17][18][19][20][21][22][23] Several studies have identified various sociodemographic risk factors that contributed to antenatal depression in developing countries. These include maternal age, [24,25] being unmarried, [26][27][28] having a lower level of education, [25,26,29] smoking, [26,30,31] consumption of alcohol, [30] being HIV infected, [31,32] poor nutritional status, [33,34] partner violent behaviour, [21,[35][36][37] and lack of partner financial support.…”
mentioning
confidence: 99%
“…Antenatal depression can have serious consequences for both the mother and the newborn. According to Indian research, the prevalence of prenatal depression ranges from 1.9 to 21.6 % [11]. The prevalence of antenatal depression in our research was 41%.…”
Section: Discussionmentioning
confidence: 45%